Precise temperature controlling algorithm for metrological adiabatic calorimeters based on proportional-integration (α) thermal energy - El Matarawy, A.; El-Dien, Eman Mohy (Journal of thermal analysis and calorimetry, 2022)
Thermal metrology laboratory at the National Institute of Standards (NIS-Egypt) has been working to realize the International Temperature Scale-1990 (Preston-Thomas in Metrologia 27:3–10, 1990). High-precision thermal control is required especially with low-temperature fixed points that were realized within adiabatic calorimeters. In this study, a new algorithm module has been developed to control precisely the accurate temperature based on equal partitioning the temperature domain to be equivalent to the sensitivity of controlling thermometer (0.00391 K −1 ). The algorithm technique is required to maintain and stabilize the temperature of an adiabatic evacuated copper can that is located inside a thermally isolated calorimeter; the modified fractional proportional-integration function and sensitivity partial temperature function (SPTF) for temperature control have been designed and developed. The improved discrete SPTF has showed a thermal stability better than 28 ± 1.8 mK at temperature extremely close to the triple point of water cell ( T cell = 273.16 K) with reliable response time within 18 ± 1 min of performance. The thermal parameters of the new adiabatic calorimeter have been calculated such as the heat capacity of the load and the thermal resistance between the regulated shield and the measuring sample. The estimated uncertainty related to the measurements has been improved to ± 0.28 mK.